Prevalence of lactose intolerance in patients with diarrhea-predominant irritable bowel syndrome: data from a tertiary center in southern China - Lishou Xiong; Yilin Wang; Xiaorong Gong; Minhu Chen (BMC, 2017)
Abstract Background Symptoms associated with lactose intolerance (LI) and diarrhea-predominant irritable bowel syndrome (IBS-D) are almost the same. These disease entities are difficult to differentiate clinically. In practice, differential diagnosis depends on self-reported patient milk intolerance. However, there is limited data on the prevalence of LI in China. The aim of this study was to investigate the prevalence of LI in IBS-D patients and asymptomatic healthy controls. Methods Lactose malabsorption (LM) was diagnosed by a lactose hydrogen breath test (HBT) and was defined by peak breath H2 excretion over the baseline level of ≥ 20 ppm. LI-related symptoms were monitored for 8 h following lactose administration. LI was defined in LM patients with positive symptoms during the observation time. Patients with IBS-D were additionally asked if they were intolerant to milk. Results A total of 109 eligible IBS-D patients (Rome III criteria) and 50 healthy controls were enrolled in this study. Except for hydrogen non-producers, the prevalence of LM did not differ between IBS-D patients and the control group (85%, 82/96 vs 72%, 34/47; P = 0.061). There was, however, a higher LI prevalence in IBS patients than in healthy subjects (45%, 43/96 vs 17%, 8/47; P = 0.002). Sensitivity, specificity, and positive and negative predictive values of self-reported milk intolerance for detecting LI were 58, 58, 53, and 63%, respectively. Conclusions Prevalence of LI is significantly higher in IBS-D patients than in healthy subjects. Self-reported milk intolerance is a poor diagnostic predictor of LI.